Prehospital Handling of Traffic Accidents in High School PGRI 4 Denpasar - Putra, I Gde Agus Shuarsedana; Maharyawan, I Wayan Agus (Jurnal Abdimas ITEKES, 2021)
Traffic accidents are the eighth leading cause of death in Indonesia. Data from the Traffic Corps of the Police of the Republic of Indonesia states that every year 28,000-38,000 people die from traffic accidents in Indonesia. This number makes Indonesia ranked first in the country with the highest ratio of deaths from traffic accidents in the world (Kompas, 2017). In 2018 there was an accident with a death toll of 261 people. The number of victims of serious injuries/hospitalization due to transportation accidents was 190 people. Bali is classified as an area with heavy traffic and has a high number of traffic accidents. One of the efforts made is to seek to reduce the number of deaths due to pre-hospital snacking errors. Efforts made in this community service program are to educate students about handling pre-hospital patients at SMA PGRI 4 Denpasar which begins with counseling about fractures and continues with the introduction of pre-hospital handlers in fracture patients. This program aims to increase knowledge about the definition of fracture and train students on pre-hospital handling in road accidents so as to reduce the death rate in accident victims due to the first mishandling on the road. In the implementation of this activity, the activity begins with the provision of a pre-test questionnaire which is filled out by the participants, then counseling about fractures is carried out using the lecture method and finally a post-test aimed at SMA PGRI 4 Denpasar students. The results of the activity showed an increase in students' knowledge about fractures and could train students about handling fractures in road accidents.